2020
DOI: 10.1161/hypertensionaha.120.15622
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Impacts of ACE (Angiotensin-Converting Enzyme) Inhibitors Versus Angiotensin II Receptor Blockers on the Risk of COVID-19 Mortality

Abstract: N/A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 5 publications
1
62
1
2
Order By: Relevance
“…One of the three reports published in Hypertension demonstrating similar conclusion as our report here. However, this study reported in a short communication with only 1 figure without detailed methodology 47 . Two reports published in JAMA and JAMA Cardiology and one retracted NEJM paper show that ARBs were not statistically significantly associated with fatal outcome of COVID-19 32 , 42 , 48 .…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…One of the three reports published in Hypertension demonstrating similar conclusion as our report here. However, this study reported in a short communication with only 1 figure without detailed methodology 47 . Two reports published in JAMA and JAMA Cardiology and one retracted NEJM paper show that ARBs were not statistically significantly associated with fatal outcome of COVID-19 32 , 42 , 48 .…”
Section: Discussionmentioning
confidence: 84%
“…There are 18 reports studying the association of ARBs and ACEI drugs with COVID-19 26 , 29 , 32 47 . Eleven out of the 18 papers reported the analysis of fatal outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2; pooled OR = 0.73, 95% CI 0.56-0.95). In a separate pooled analysis of 11 studies that provided adjusted HRs, with 26,598 COVID-19 patients being analyzed [36,54,56,57,59,67,69,70,72,74,77], the use of an ACEI/ARB was significantly associated with lower risk of mortality compared to the non-use of an ACEI/ARB (Supplementary Figure S1; pooled HR = 0.75, 95% CI 0.60-0.95). The funnel plot was used to detect the publication bias and revealed some degree of asymmetry (Supplementary Figure S3 and S4).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Subgroup analysis that was limited to studies that provided adjusted mortality estimates for exclusively hypertensive patients with COVID-19 demonstrated a statistically non-significant association with lower odds of mortality (Supplementary Table S2; pooled OR = 0.73, 95% CI 0.52-1.02; six studies [66,75,78,88,89,92]) and a statistically significant association with lower risk of mortality (Supplementary Table S2; pooled HR = 0.39, 95% CI 0.20-0.77; five studies [36,54,56,57,72]) among users of ACEIs/ARBs compared to the non-users. Table S2; pooled OR = 0.89, 95% CI 0.66-1.21) [86,88,89,92] in the users of ACEIs/ARBs compared to the non-users.…”
Section: Mortality Associated With the Use Of Ras Inhibitors In Covidmentioning
confidence: 99%